"Bem me Quer" (Love me) Program: a tool to decrease fetal and infant mortality in the city of Santa Cruz do Sul/RS - Maria Elijara Sales Snovarski (Universidade de Santa Cruz do Sul, 2013)
KEYWORDS Infant and fetal mortality Epidemiological surveillance